Optimizing the Use of Lontara Fonts and Characters in Learning Local Content of Bugis Local Language at Junior High School Level in Sidenreng Rappang - Saleh, Firman -; Haeruddin, Haeruddin; Agussalim, Andi; Vieriawan, Andi; Yusuf, Yusuf (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
This research aims to optimize the utilization of Lontara fonts and characters in the development of teaching materials and local culture-based learning media. It is expected to increase students' learning motivation by presenting learning materials in accordance with the trend of the times and current needs. The implementation of this teaching strategy involves the use of computers as an effective source of instruction and multimedia as a learning motivation tool that can accommodate modern learning styles. With this innovation, it is expected that the ability to use multimedia in the learning process will improve, which in turn will make students more enthusiastic in learning Bugis local content at the junior high school level. Overall, the main contribution of this research is to create relevant teaching strategies in learning, utilize computers as an effective source of instruction, utilize multimedia as a learning motivation tool, and increase students' enthusiasm in learning Bugis local content.